Patients' expectations about total knee arthroplasty outcomes. (13th February 2015) - de Achaval, Sofia; Kallen, Michael A.; Amick, Benjamin; Landon, Glenn; Siff, Sherwin; Edelstein, David; Zhang, Hong; Suarez‐Almazor, Maria E.
Abstract: Objective: The aim of this study was to ascertain Patients' pre‐operative expectations of total knee arthroplasty (TKA) recovery. Methods: Two hundred and thirty‐six patients with knee osteoarthritis (OA) who underwent TKA completed self‐administered questionnaires before their surgery. Patients' expectations of time to functional recovery were measured using an ordinal time–response scale to indicate expected time to recovery for each of 10 functional activities. Expected time to recovery was dichotomized into short‐ and long‐term expectations for recovery of each activity using median responses. Knee pain and function were ascertained using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Other measures included the SF‐36, the Depression, Anxiety and Stress Scale (DASS) and the Medical Outcomes Study Social Support Survey (MOS‐SSS). Multivariate logistic regression was used to identify pre‐operative characteristics associated with short‐ vs. long‐term expectations. Results: Sixty‐five percent of the patients were females and 70% Whites; mean age was 65 years. Patients were optimistic about their time to functional recovery: over 65% of patients expected functional recovery within 3 months. Over 80% of the patients expected to perform 8 of the 10 activities within 3 months. Patients who expected to be able to perform the functional activities in <6 weeks were more likely to be younger, male, and have lower self‐reported pain and better general health before surgery compared to those who expected to be able to perform the activities 3 months post‐surgery or later. Conclusion: Pre‐operative patient characteristics may be important to evaluate when considering individual Patients' expectations of post‐operative outcomes.